Gallium(III) triflate-catalyzed synthesis of quinoxaline derivatives - Cai, Jing-Jing; Zou, Jian-Ping; Pan, Xiang-Qiang; Zhang, Wei (Tetrahedron letters, 2008)
Gallium(III) triflate-catalyzed reactions of phenylene-1,2-diamines and 1,2-diketones produce quinoxalines in excellent to quantitative yields. The reactions proceed with 1 mol % catalyst in ethanol at room temperature. The catalyst can be recycled for at least 10 times.